Biocontrol Potential of some Entomopathogenic Fungi against The Cotton Leaf Worm Spodoptera littoralis in vitro (Journal of Nuclear Technology in Applied Science, 2019)
The objective of this study was to isolate and identify the entomopathogenic fungi as biocontrol agents and to evaluate their pathogenicity against the cotton leaf worm, Spodoptera littoralis (Boisd.). Six strains of fungi were isolated from healthy and infected plants using dilution plate method. Czapek’s agar supplemented with 0.5 % yeast extract and potato dextrose agar, amended with rose bengal (1/15000) and chloramphenicol (50 ppm) was used for primary isolation. Aspergillus tamarii, Aspergillus parasiticus, pencillium sp., Trichoderma harzianum,Cladosporium sp .and Rhizopus sp. were isolated . Results showed that A. parasiticus , A. tamarii, T. harzianum and Pencillium sp. are the most promonent so in this study we test their virulence against third instar larvae of the cotton leaf worm the mortality percentage were calculated for each fungus using 1×106, 1×107 and 1×108 spore per ml. It is clear from the results that the mortality percentage increased with elapsing time. The high mortality percentage recorded is 86.66% for A.tamarii at 1×108 spore/ ml then 83.33% with A.parasiticus at 1×107 spore/ml, 80% for T. harizianum at 1×106 spore/ml and 40% at 1×107spore/ml for Pencillium sp. Comparison to these fungi clear that concentration 107 give the highest mortality percentage to the cotton leaf worm for all except A.tamarii .Then screening to the ability of these fungi to produce protease enzyme reveals that all of them produce protease enzyme except Pencillium sp. Gamma irradiation was used to enhance the protease enzyme activity and consequently increase the mortality percentageThe dose level of 1200 Gy increase protease activity of A. tamarii from 0.433 to 1.366 so mortality percentage of third instar larvae of Spodoptera littoralis increased from 43.33 % to 86.66 % at concentration 1×107 of spore suspension irradiated with 1200 Gy dose level..
Keywords: Entomopathogenic Fungi; Spodoptera Littoralis; Biocontrol; Czapek›s Agar; Protease Enzyme; Gamma Irradiation